How broad is the selfing syndrome? Insights from convergent evolution of gene expression across species and tissues in the Capsella genus. Issue 6 (30th September 2022) - Zhang, Zebin; Kryvokhyzha, Dmytro; Orsucci, Marion; Glémin, Sylvain; Milesi, Pascal; Lascoux, Martin
Summary: The shift from outcrossing to selfing is one of the main evolutionary transitions in plants. It is accompanied by profound effects on reproductive traits, the so‐called selfing syndrome. Because the transition to selfing also implies deep genomic and ecological changes, one also expects to observe a genomic selfing syndrome. We took advantage of the three independent transitions from outcrossing to selfing in the Capsella genus to characterize the overall impact of mating system change on RNA expression, in flowers but also in leaves and roots. We quantified the extent of both selfing and genomic syndromes, and tested whether changes in expression corresponded to adaptation to selfing or to relaxed selection on traits that were constrained in outcrossers. Mating system change affected gene expression in all three tissues but more so in flowers than in roots and leaves. Gene expression in selfing species tended to converge in flowers but diverged in the two other tissues. Hence, convergent adaptation to selfing dominates in flowers, whereas genetic drift plays a more important role in leaves and roots. The effect of mating system transition is not limited to reproductive tissues and corresponds to both adaptation to selfing and relaxed selection on previously constrained traits.